Chromosome replication during the division cycle in slowly growing, steady-state cultures of three Escherichia coli B/r strains. - Kubitschek, H E (1978)
The period of DNA synthesis C during the cell cycle was determined over a broad range of generation times in slowly growing, steady-state batch cultures in the exponential phase and in chemostat cultures of three strains of Escherichia coli, strains B/r A, B/r K, and B/r TT, utilizing measurements of average amounts of DNA per cell and cell survival after radioactive decay of 125I incorporated into the DNA of synthesizing cells. At each growth rate, values for cell survival and for C periods were the same within experimental errors for the three strains. The length of the DNA synthesis period increased linearly with generation (doubling) time T of the culture and approached a limiting value of C = 0.36T at very long generation times. In very slowly growing cultures, DNA replication was limited almost entirely to the final third of the cell cycle. D periods, between termination of DNA replication and cell division, were found to be relatively short at all growth rates for each strain. Average amounts of DNA per cell measured in slowly growing cultures of strains B/r A and B/r TT were indistinguishable from results for strain B/r K at the same growth rates. Amounts of DNA per cell calculated from the cell survival values alone are completely consistent with the measured DNA per cell.